2021
DOI: 10.1016/j.artd.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

What is the Effect of Posterior Osteophytes on Flexion and Extension Gaps in Total Knee Arthroplasty? A Cadaveric Study

Abstract: Background: Posterior compartment knee osteophytes may pose a challenge in achieving soft-tissue balance during total knee arthroplasty (TKA). Obtaining symmetry of flexion and extension gaps involves balance of both bony and soft-tissue structures. We hypothesize that space-occupying posteromedial femoral osteophytes affect soft-tissue balance. Methods: Five cadaveric limbs were acquired. Computed tomography scans were obtained to define the osseous contours. Three-dimensionally printed, specimen-specific syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These differences may be due to the influence of preoperative flexion contracture, or a tight posterior capsule in extension due to posterior osteophytes, which increase knee stiffness and limit ROM in extension and early flexion. 22 Posterior capsule releases, posterior osteophyte removal, and implant trialing performed after femoral resection to increase passive knee extension may explain why knee stiffness was more uniform throughout flexion post-resection. 23 Furthermore, Bellemans et al reported that ligament stress relaxation does occur perioperatively during the course of a TKA procedure and results in an increase in mediolateral gaps of 1 mm and an increase in maximal passive extension of 3 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be due to the influence of preoperative flexion contracture, or a tight posterior capsule in extension due to posterior osteophytes, which increase knee stiffness and limit ROM in extension and early flexion. 22 Posterior capsule releases, posterior osteophyte removal, and implant trialing performed after femoral resection to increase passive knee extension may explain why knee stiffness was more uniform throughout flexion post-resection. 23 Furthermore, Bellemans et al reported that ligament stress relaxation does occur perioperatively during the course of a TKA procedure and results in an increase in mediolateral gaps of 1 mm and an increase in maximal passive extension of 3 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…However, for osteophytes >10 mm, the ME gap increased more asymmetrically than the LE, MF, and LF gaps ( p < 0.05). Holst et al [ 20 ] conducted a cadaveric study to evaluate the effects of 10 mm and 15 mm 3D-printed osteophyte-mimicking blocks on the medial and lateral contact forces using Verasense (OrthoSensor-Dania Beach, FL, USA). Although there were no significant differences between the 10 mm and 15 mm blocks on the medial contact forces, the presence of blocks caused an asymmetric contact force between the ME and LE.…”
Section: Discussionmentioning
confidence: 99%